Kerusakan di Bumi Dalam Alquran: Kajian Tafsir Tematik dalam Tafsir Anwar al-Tanzil wa Asrar al-Ta’wil Karya al-Baydawi - Nur Rofiq; Didi Junaedi; Muhammad Maimun (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2018)
This study is based on the increasing environmental destruction in this world, like forests in Indonesia are getting smaller, floods, and coral reef damage. Besides that, social behavior damage impacts the surrounding environment. The attitude of dishonesty, oppression, hedonism and others also adds to the list of damage on this earth. The Qur'an has mentioned that thi universe is destined for mankind. Therefore, God has created man as His-khalifah on earth, and given the responsibility for it. Therefore, good and bad the environment is depends on human behavior because humans have also been given a mind is not given to other living beings.Â